Preparation method of vanadium oxide-carbon quantum dot composite nanobelt
Through the solvent-thermal synthesis method, the problem of vanadium oxide and carbon quantum dots cannot be fully contacted, and a vanadium oxide-carbon quantum dot composite nanoribbon with good morphology and structural uniformity was prepared, achieving efficient preparation and application prospects of composite nanomaterials.
Patent Information
- Application Number
- CN202411904119.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
AI Technical Summary
Among the existing vanadium oxide-carbon quantum dot composite nanomaterials, vanadium oxide cannot fully contact the carbon quantum dots, the composite nanomaterial size is too large, the morphology and structural uniformity are poor, and the preparation process is complicated.
By using the solvent-thermal synthesis method, the precursor liquid is prepared by treating the surface of the carbon quantum dots, and solvothermal reaction is carried out under specific temperature and time conditions to obtain a vanadium oxide-carbon quantum dot composite nanoribbon.
Full contact between vanadium oxide and carbon quantum dots was achieved, and composite nanoribbons with good morphology and structural uniformity were prepared. The size was small, the belt was large, and the process was simple, which avoided the use of hard templates and improved the purity of the product.
Smart Images

Figure CN119706936A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a carbon quantum dot composite nanobelt. Background Art
[0002] Vanadium oxide-carbon composite materials are widely used in secondary energy storage batteries, aqueous batteries, new sensors, optoelectronic devices, catalysis and other fields. Vanadium oxide is recognized as one of the ideal materials in the field of sensors and chemical catalysis, and has attracted much attention from the industry and scientific research community in recent years. For example, vanadium oxide, as an important positive electrode material, can well deintercalate Zn 2+ , and is considered to be an excellent aqueous zinc ion material. Vanadium oxide has the advantages of high theoretical capacity, moderate discharge potential, high element reserves, and low cost, and has good application prospects in the fields of lithium-ion batteries, sodium-ion batteries, and aqueous zinc-ion batteries.
[0003] Nanomaterials have become a hot spot in material synthesis in recent years due to their unique properties (high surface effect, volume effect, small size effect, quantum size effect and macroscopic quantum tunneling effect). At present, the synthesis of vanadium oxide-carbon composite nanomaterials is mainly achieved through solvent thermal synthesis, chemical vapor deposition, recrystallization or electrochemical deposition. In the composite nanomaterials of vanadium pentoxide and carbon quantum dots prepared by the existing preparation process, vanadium oxide and carbon quantum dots cannot fully contact each other, and the size of the composite nanomaterial is too large. The electrical conductivity and ion conductivity of vanadium oxide are poor, so carbon components are required to improve its electrical conductivity and increase its active sites for ion embedding. The inability of vanadium oxide to fully contact carbon quantum dots will lead to an insignificant improvement in the electrical conductivity of the composite nanomaterial, thereby affecting the cycle stability. In addition, the existing process is complex and lacks the potential for production expansion, and the morphology and structural uniformity of the prepared nanocomposite materials are poor. Summary of the invention
[0004] The present invention aims to solve the problems that vanadium oxide and carbon quantum dots in existing vanadium oxide-carbon quantum dot composite nanomaterials cannot fully contact each other, the composite nanomaterials are too large in size, the morphology and structural uniformity are poor, and the preparation process is complicated, and further provides a method for preparing vanadium oxide-carbon quantum dot composite nanobelts.
[0005] A method for preparing a vanadium oxide-carbon quantum dot composite nanobelt is carried out according to the following steps:
[0006] 1. Treat the surface of carbon quantum dots:
[0007] The carbon quantum dot aqueous solution is added to concentrated nitric acid and heated and stirred, then the pH value is adjusted to neutral, sodium borohydride is added and stirred, and finally heated and concentrated to obtain a reduced carbon quantum dot solution;
[0008] 2. Preparation of precursor solution:
[0009] Mixing a vanadium source, hydrogen peroxide and a reduced carbon quantum dot solution to obtain a mixed solution, adding anhydrous ethanol to the mixed solution and mixing evenly, then adding oleic acid and mixing evenly, and finally adding sodium oleate and mixing evenly to obtain a precursor solution;
[0010] 3. Solvothermal reaction:
[0011] Under the condition of temperature of 195° C. to 215° C., the precursor solution is subjected to solvent thermal reaction for 16 h to 24 h to obtain a crude product solution, and the crude product solution is centrifuged, washed and dried to obtain a vanadium oxide-carbon quantum dot composite nanobelt.
[0012] The beneficial effects of the present invention are:
[0013] 1. The present invention provides a method for preparing vanadium oxide-carbon quantum dot composite nanobelts. By using a solvent thermal method, by adjusting the ratio of vanadium oxide-carbon quantum dot precursor solution, composite nanobelts with different carbon quantum dot contents can be obtained. By adjusting the concentration of the precursor solution, the temperature and time of the solvent thermal, the morphology of the nanobelt can be controlled, the morphology and structure are uniform, the size of the composite nanomaterial is small, the belt length is greater than 20μm, and the belt width is only 40nm to 70nm.
[0014] 2. The present invention provides a method for preparing vanadium oxide-carbon quantum dot composite nanobelts, which does not require any hard template, has a simple preparation process, avoids the introduction of impurities during the addition and removal of the hard template, eliminates the process of product purification, and has high product purity.
[0015] 3. The present invention provides a method for preparing a vanadium oxide-carbon quantum dot composite nanobelt, in which the carbon quantum dots are not simply coated on the vanadium oxide nanobelt, but are directly embedded in the nanobelt, which not only allows the vanadium oxide and the carbon quantum dots to fully contact, but also improves the degree of bonding between the carbon quantum dots and the vanadium oxide.
[0016] 4. The present invention provides a method for preparing a vanadium oxide-carbon quantum dot composite nanobelt. The prepared vanadium oxide-based composite nanobelt can be used as a positive electrode material for sodium ion batteries and a positive electrode material for aqueous zinc ions.
[0017] 5. The present invention provides a method for preparing vanadium oxide-carbon quantum dot composite nanobelts, which realizes the first synthesis of vanadium oxide-carbon quantum dot composite nanobelts, fills the gap in the international preparation of vanadium oxide-carbon quantum dot composite nanobelts, and has important reference value for the commercial application of vanadium oxide-based nanomaterials in energy storage devices and smart devices.
[0018] The present invention uses a solvent thermal synthesis method to prepare for the first time a composite nanobelt structure in which carbon quantum dots are embedded in a vanadium oxide bulk phase, which will have good application prospects in nano-optical devices, electronic devices, electrochemical sensor devices, transistors, etc., and will play an important guiding role in achieving industrial production.
[0019] The invention is used for a method for preparing a vanadium oxide-carbon quantum dot composite nanobelt. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 HRTEM image of the vanadium oxide-carbon quantum dot composite nanobelt prepared in Example 1;
[0021] Figure 2 This is a SEM image of the vanadium oxide-carbon quantum dot composite nanobelt prepared in Example 1;
[0022] Figure 3 The cyclic stability curve of the vanadium oxide-carbon quantum dot composite nanobelt prepared in Example 1 as a positive electrode material for a sodium ion battery;
[0023] Figure 4 The cyclic stability curve of the vanadium oxide-carbon quantum dot composite nanobelt prepared in Example 1 as the positive electrode material of aqueous zinc ion battery;
[0024] Figure 5 The SEM image and corresponding mapping image of the vanadium oxide-carbon quantum dot composite nanobelt prepared in Example 1. DETAILED DESCRIPTION
[0025] Specific implementation method 1: This implementation method is a method for preparing a vanadium oxide-carbon quantum dot composite nanobelt, which is carried out according to the following steps:
[0026] 1. Treat the surface of carbon quantum dots:
[0027] The carbon quantum dot aqueous solution is added to concentrated nitric acid and heated and stirred, then the pH value is adjusted to neutral, sodium borohydride is added and stirred, and finally heated and concentrated to obtain a reduced carbon quantum dot solution;
[0028] 2. Preparation of precursor solution:
[0029] Mixing a vanadium source, hydrogen peroxide and a reduced carbon quantum dot solution to obtain a mixed solution, adding anhydrous ethanol to the mixed solution and mixing evenly, then adding oleic acid and mixing evenly, and finally adding sodium oleate and mixing evenly to obtain a precursor solution;
[0030] 3. Solvothermal reaction:
[0031] Under the condition of temperature of 195° C. to 215° C., the precursor solution is subjected to solvent thermal reaction for 16 h to 24 h to obtain a crude product solution, and the crude product solution is centrifuged, washed and dried to obtain a vanadium oxide-carbon quantum dot composite nanobelt.
[0032] The beneficial effects of this embodiment are:
[0033] 1. This embodiment provides a method for preparing vanadium oxide-carbon quantum dot composite nanobelts. By using a solvent thermal method, by adjusting the ratio of vanadium oxide-carbon quantum dot precursor solution, composite nanobelts with different carbon quantum dot contents can be obtained. By adjusting the concentration of the precursor solution, the temperature and time of the solvent thermal, the morphology of the nanobelts can be controlled, the morphology and structure are uniform, the size of the composite nanomaterial is small, the belt length is greater than 20μm, and the belt width is only 40nm to 70nm.
[0034] 2. This embodiment provides a method for preparing vanadium oxide-carbon quantum dot composite nanobelts, which does not require any hard template, has a simple preparation process, avoids the introduction of impurities during the addition and removal of the hard template, eliminates the process of product purification, and has high product purity.
[0035] 3. In the method for preparing a vanadium oxide-carbon quantum dot composite nanobelt provided in this embodiment, the carbon quantum dots are not simply coated on the vanadium oxide nanobelt, but are directly embedded in the nanobelt, which not only allows the vanadium oxide and the carbon quantum dots to fully contact, but also improves the degree of bonding between the carbon quantum dots and the vanadium oxide.
[0036] 4. This embodiment provides a method for preparing a vanadium oxide-carbon quantum dot composite nanobelt. The prepared vanadium oxide-based composite nanobelt can be used as a positive electrode material for sodium ion batteries and a positive electrode material for aqueous zinc ions.
[0037] 5. The preparation method of a vanadium oxide-carbon quantum dot composite nanobelt provided in this embodiment realizes the first synthesis of vanadium oxide-carbon quantum dot composite nanobelt, fills the gap in the international preparation of vanadium oxide-carbon quantum dot composite nanobelt, and has important reference value for the commercial application of vanadium oxide-based nanomaterials in energy storage devices and smart devices.
[0038] This embodiment uses a solvent thermal synthesis method to prepare for the first time a composite nanobelt structure of carbon quantum dots embedded in a vanadium oxide bulk phase, which will have good application prospects in nano-optical devices, electronic devices, electrochemical sensor devices, transistors, etc., and will play an important guiding role in achieving industrial production.
[0039] Specific embodiment 2: This embodiment is different from specific embodiment 1 in that the particle size of the carbon quantum dots in the carbon quantum dot aqueous solution described in step 1 is 10 nm to 15 nm. The rest is the same as specific embodiment 1.
[0040] Specific implementation method three: This implementation method is different from specific implementation method one or two in that: the concentration of carbon quantum dots in the carbon quantum dot aqueous solution described in step one is 5mg / mL to 10mg / mL; the concentration of concentrated nitric acid described in step one is 2mol / L to 4mol / L; the concentration of the reduced carbon quantum dot solution described in step one is 5mg / mL to 10mg / mL. Others are the same as specific implementation method one or two.
[0041] Specific embodiment 4: This embodiment differs from Specific embodiments 1 to 3 in that: the volume ratio of the carbon quantum dot aqueous solution to concentrated nitric acid in step 1 is 1:(2-5); the mass ratio of the volume of the carbon quantum dot aqueous solution to sodium borohydride in step 1 is 1 mL:(2-5) mg. Others are the same as Specific embodiments 1 to 3.
[0042] Specific embodiment 5: This embodiment is different from specific embodiments 1 to 4 in that: in step 1, the carbon quantum dot aqueous solution is added to concentrated nitric acid, stirred for 20min to 120min at a temperature of 85°C to 98°C and a stirring speed of 1200r / min to 1500r / min, then the pH value is adjusted to neutral with sodium carbonate, and then sodium borohydride is added, stirred for 600min to 720min at a temperature of 5°C to 25°C and a stirring speed of 1200 / min to 1500r / min, and finally heated and concentrated at a temperature of 85°C to 97°C. Others are the same as specific embodiments 1 to 4.
[0043] Specific embodiment 6: This embodiment is different from specific embodiments 1 to 5 in that the vanadium source in step 2 is one or a combination of vanadium, ammonium metavanadate, vanadium chloride, vanadium oxybenzoate, vanadium oxyacetylacetonate and vanadium tripropoxide. The rest is the same as specific embodiments 1 to 5.
[0044] Specific implementation method 7: This implementation method is different from one of specific implementation methods 1 to 6 in that: the mass percentage of hydrogen peroxide described in step 2 is 30%; the volume ratio of the mole number of the vanadium source described in step 2 to hydrogen peroxide is 1mmol:(0.5-2)mL; the volume ratio of the mole number of the vanadium source described in step 2 to the reduced carbon quantum dot solution is 1mmol:(0.5-1)mL; the volume ratio of the mixed solution described in step 2 to anhydrous ethanol is 1:(5-20); the volume ratio of the mole number of the vanadium source described in step 2 to oleic acid is 1mmol:(10-20)mL; the mass ratio of the mole number of the vanadium source described in step 2 to sodium oleate is 1mmol:(5-120)mg. The others are the same as specific implementation methods 1 to 6.
[0045] Specific embodiment eight: This embodiment differs from specific embodiments one to seven in that: in step two, at a rotation speed of 1200r / min to 1500r / min, the vanadium source, hydrogen peroxide and the reduced carbon quantum dot solution are mixed for 20min to 120min to obtain a mixed solution, at a rotation speed of 1200r / min to 1500r / min, anhydrous ethanol is added to the mixed solution and mixed for 5h to 7h, then at a rotation speed of 1200r / min to 1500r / min, oleic acid is added and mixed for 20min to 120min, and finally at a rotation speed of 1200r / min to 1500r / min, sodium oleate is added and mixed for 300min to 600min to obtain a precursor solution. The rest is the same as specific embodiments one to seven.
[0046] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that: in step 3, the temperature of the precursor solution is raised to 195° C. to 215° C. at a heating rate of 0.5° C. / min to 3° C. / min. The rest is the same as specific embodiments 1 to 8.
[0047] Specific embodiment 10: This embodiment differs from specific embodiments 1 to 9 in that the centrifugation, washing and drying described in step 3 are specifically carried out according to the following steps: centrifugation for 20 min to 90 min at a rotation speed of 1200 r / min to 1500 r / min, then washing with anhydrous ethanol and ultrapure water in turn, and finally drying for 12 h to 18 h at a temperature of 60° C. to 75° C. The rest is the same as specific embodiments 1 to 9.
[0048] The following examples are used to verify the beneficial effects of the present invention:
[0049] Embodiment 1:
[0050] A method for preparing a vanadium oxide-carbon quantum dot composite nanobelt is carried out according to the following steps:
[0051] 1. Treat the surface of carbon quantum dots:
[0052] The carbon quantum dot aqueous solution was added to concentrated nitric acid, stirred for 30 minutes at a temperature of 95°C and a stirring speed of 30 r / min, and then the pH value was adjusted to neutral with sodium carbonate, and then sodium borohydride was added, stirred for 700 minutes at a temperature of 10°C and a stirring speed of 1200 r / min, and finally heated and concentrated at a temperature of 90°C to obtain a reduced carbon quantum dot solution;
[0053] The particle size of the carbon quantum dots in the carbon quantum dot aqueous solution is 10nm to 15nm; the concentration of the carbon quantum dots in the carbon quantum dot aqueous solution is 5mg / mL; the concentration of the concentrated nitric acid is 4mol / L; the concentration of the reduced carbon quantum dot solution is 5mg / mL; the volume ratio of the carbon quantum dot aqueous solution to the concentrated nitric acid is 1:5; the mass ratio of the volume of the carbon quantum dot aqueous solution to sodium borohydride is 1mL:3mg;
[0054] 2. Preparation of precursor solution:
[0055] At a rotation speed of 1200 r / min, the vanadium source, hydrogen peroxide and the reduced carbon quantum dot solution were mixed for 60 min to obtain a mixed solution, anhydrous ethanol was added to the mixed solution at a rotation speed of 1200 r / min and mixed for 5 h, then oleic acid was added at a rotation speed of 1200 r / min and mixed for 50 min, and finally sodium oleate was added at a rotation speed of 1200 r / min and mixed for 360 min to obtain a precursor solution;
[0056] The vanadium source is ammonium metavanadate; the mass percentage of the hydrogen peroxide is 30%; the volume ratio of the molar number of the vanadium source to the hydrogen peroxide is 1mmol:1mL; the volume ratio of the vanadium source to the molar number of the reduced carbon quantum dot solution is 1mmol:1mL; the volume ratio of the mixed solution to anhydrous ethanol is 1:8; the volume ratio of the molar number of the vanadium source to oleic acid is 1mmol:12mL; the mass ratio of the molar number of the vanadium source to sodium oleate is 1mmol:22mg;
[0057] 3. Solvothermal reaction:
[0058] The precursor solution was heated to 200°C at a heating rate of 2°C / min, and then solvent thermally reacted for 16 hours at 200°C to obtain a crude product solution. The crude product solution was centrifuged at a rotation speed of 1200r / min for 30 minutes, and then washed with anhydrous ethanol and ultrapure water in turn, and finally dried at 60°C for 12 hours to obtain vanadium oxide-carbon quantum dot composite nanobelts.
[0059] Figure 1 This is the HRTEM image of the vanadium oxide-carbon quantum dot composite nanobelt prepared in Example 1; as can be seen from the figure, the composite nanobelt is composed of V2O5 lattice and carbon quantum dots, and the V2O5 nanocrystals are evenly distributed in the nanobelt, that is, the carbon quantum dots are embedded in the nanobelt.
[0060] Figure 2This is a SEM image of the vanadium oxide-carbon quantum dot composite nanobelt prepared in Example 1; as can be seen from the figure, the composite nanomaterial is a ribbon structure with good morphology and structural uniformity, a ribbon length greater than 20 μm, and a bandwidth of 40 nm to 70 nm.
[0061] The vanadium oxide-carbon quantum dot composite nanobelt prepared in Example 1 was directly used as the working electrode of the battery, sodium foil was used as the negative electrode of the battery, 1 mol / L sodium perchlorate EC:DEC:FEC solution (volume ratio of 1:1:0.05) was used as the electrolyte, and glass fiber separator (GF / D) was used as the battery separator. It was encapsulated in a CR2016 button battery shell and assembled into a half-battery for testing. The charge and discharge test was performed using a Xinwei battery tester, and the battery test current density was 100mAg -1 . Figure 3 The cyclic stability curve of the vanadium oxide-carbon quantum dot composite nanobelt prepared in Example 1 as a positive electrode material for a sodium ion battery; As can be seen from the figure, the composite nanobelt as a positive electrode material for a sodium ion battery is 100mAg -1 The reversible specific capacity is greater than 200 mAh g -1 .
[0062] The vanadium oxide-carbon quantum dot composite nanobelt prepared in Example 1 was directly used as the positive electrode of the battery, high-purity zinc foil was used as the negative electrode of the battery, 1 mol / L zinc perchlorate aqueous solution was used as the electrolyte, glass fiber separator (GF / A) was used as the battery separator, and OL-ALM aluminum-plastic film was used as the soft-pack battery shell. The soft-pack battery was assembled for testing. The charge and discharge test was performed using a Xinwei battery tester, and the battery test current density was 100mAg -1 . Figure 4 The cyclic stability curve of the vanadium oxide-carbon quantum dot composite nanobelt prepared in Example 1 as the positive electrode material of the aqueous zinc ion battery; As can be seen from the figure, the composite nanobelt as the positive electrode material of the aqueous zinc ion battery is 100mAg -1 The reversible specific capacity is greater than 300 mAh g -1 .
[0063] Figure 5 The SEM and corresponding mapping images of the vanadium oxide-carbon quantum dot composite nanobelt prepared in Example 1. As can be seen from the figure, the composite nanobelt is uniformly composed of vanadium, oxygen and carbon elements, indicating that the vanadium oxide and carbon quantum dots are uniformly distributed in the composite nanobelt.
Claims
1. A method for preparing vanadium oxide-carbon quantum dot composite nanobelts, characterized in that It is carried out in the following steps:
1. Treat the surface of carbon quantum dots: The carbon quantum dot aqueous solution is added to concentrated nitric acid and heated and stirred, then the pH value is adjusted to neutral, sodium borohydride is added and stirred, and finally heated and concentrated to obtain a reduced carbon quantum dot solution; 2. Preparation of precursor solution: Mixing a vanadium source, hydrogen peroxide and a reduced carbon quantum dot solution to obtain a mixed solution, adding anhydrous ethanol to the mixed solution and mixing evenly, then adding oleic acid and mixing evenly, and finally adding sodium oleate and mixing evenly to obtain a precursor solution; 3. Solvothermal reaction: Under the condition of temperature of 195° C. to 215° C., the precursor solution is subjected to solvent thermal reaction for 16 h to 24 h to obtain a crude product solution, and the crude product solution is centrifuged, washed and dried to obtain a vanadium oxide-carbon quantum dot composite nanobelt.
2. The method for preparing a vanadium oxide-carbon quantum dot composite nanobelt according to claim 1, characterized in that The particle size of the carbon quantum dots in the carbon quantum dot aqueous solution described in step 1 is 10nm to 15nm.
3. The method for preparing a vanadium oxide-carbon quantum dot composite nanobelt according to claim 1, characterized in that The concentration of carbon quantum dots in the carbon quantum dot aqueous solution described in step one is 5 mg / mL to 10 mg / mL; the concentration of concentrated nitric acid described in step one is 2 mol / L to 4 mol / L; the concentration of the reduced carbon quantum dot solution described in step one is 5 mg / mL to 10 mg / mL.
4. The method for preparing a vanadium oxide-carbon quantum dot composite nanobelt according to claim 3, characterized in that The volume ratio of the carbon quantum dot aqueous solution described in step one to concentrated nitric acid is 1:(2-5); the mass ratio of the volume of the carbon quantum dot aqueous solution described in step one to sodium borohydride is 1 mL:(2-5) mg.
5. The method for preparing a vanadium oxide-carbon quantum dot composite nanobelt according to claim 1, characterized in that In step 1, the carbon quantum dot aqueous solution is added to concentrated nitric acid, stirred for 20 min to 120 min at a temperature of 85°C to 98°C and a stirring speed of 1200 r / min to 1500 r / min, and then the pH value is adjusted to neutral with sodium carbonate, and then sodium borohydride is added, stirred for 600 min to 720 min at a temperature of 5°C to 25°C and a stirring speed of 1200 / min to 1500 r / min, and finally heated and concentrated at a temperature of 85°C to 97°C.
6. The method for preparing a vanadium oxide-carbon quantum dot composite nanobelt according to claim 1, characterized in that The vanadium source described in step 2 is one of vanadium element, ammonium metavanadate, vanadium chloride, vanadium oxybenzoate, vanadium oxyacetylacetonate and vanadium tripropoxide or a combination of several thereof.
7. The method for preparing a vanadium oxide-carbon quantum dot composite nanobelt according to claim 1, characterized in that The mass percentage of the hydrogen peroxide described in step 2 is 30%; the volume ratio of the molar number of the vanadium source described in step 2 to the hydrogen peroxide is 1mmol:(0.5-2)mL; the volume ratio of the molar number of the vanadium source described in step 2 to the reduced carbon quantum dot solution is 1mmol:(0.5-1)mL; the volume ratio of the mixed solution described in step 2 to anhydrous ethanol is 1:(5-20); the volume ratio of the molar number of the vanadium source described in step 2 to oleic acid is 1mmol:(10-20)mL; the mass ratio of the molar number of the vanadium source described in step 2 to sodium oleate is 1mmol:(5-120)mg.
8. The method for preparing a vanadium oxide-carbon quantum dot composite nanobelt according to claim 1, characterized in that In step 2, at a rotation speed of 1200 r / min to 1500 r / min, the vanadium source, hydrogen peroxide and the reduced carbon quantum dot solution are mixed for 20 min to 120 min to obtain a mixed solution, at a rotation speed of 1200 r / min to 1500 r / min, anhydrous ethanol is added to the mixed solution and mixed for 5 h to 7 h, then at a rotation speed of 1200 r / min to 1500 r / min, oleic acid is added and mixed for 20 min to 120 min, and finally at a rotation speed of 1200 r / min to 1500 r / min, sodium oleate is added and mixed for 300 min to 600 min to obtain a precursor solution.
9. The method for preparing a vanadium oxide-carbon quantum dot composite nanobelt according to claim 1, characterized in that In step 3, the precursor solution is heated to 195°C to 215°C at a heating rate of 0.5°C / min to 3°C / min.
10. The method for preparing a vanadium oxide-carbon quantum dot composite nanobelt according to claim 1, characterized in that The centrifugation, washing and drying described in step three are specifically carried out according to the following steps: centrifugation for 20min to 90min at a rotation speed of 1200r / min to 1500r / min, then washing with anhydrous ethanol and ultrapure water in turn, and finally drying at a temperature of 60℃ to 75℃ for 12h to 18h.